Assessment of Final Year Dental Students' Views of Science Education in Dental Implants - MajidReza Mokhtari; Ali Foroozanfar; Fatemeh Farazi (Mashhad University of Medical Sciences, 2012)
Introduction: The aim of the present study was to evaluate the dental student's concepts about dental implant education which can be used in dentistry doctorate curriculum revision and could be useful for professors of periodontology, prosthodontics and maxillofacial surgery.Materials & Methods: This was an educational research which was conducted in Mashhad dental school in 2011 and 58 end year dental students were participated in this study and filled out questionnaires about dental implant education and the concepts of these students about theoretical and practical aspects of dental implant education were evaluated.Results: A total of 98.27% of the students were agreed about education of simple implant surgery so that they could put a simple implant and 87.94% of the students were agreed about education of dental implant as a single course credit and about creation of a dental educational group, 96.56% were agreed. About dental implant educational topics, the most educational need was education of principles of implant surgery followed by education of putting a simple frontal implant, and the least, was introduction and history of dental implants.Conclusions: Because of necessity of development for new sciences in order to promote health in the society, education of dental implant for general dentistry students and revision of general dentistry curriculum seems necessary.